LYME DISEASE AS A PUBLIC HEALTH CHALLENGE: A REVIEW OF RECENT EVIDENCE - Karol Chromiak; Marcelina Podleśna; Kacper Curzytek; Aleksandra Stępień; Kacper Bączek; Kacper Bluczak (International Journal of Innovative Technologies in Social Science, 2026)
Lyme disease, primarily caused by the spirochete Borrelia burgdorferi transmitted by ticks of the genus Ixodes, is a growing public health problem in many regions of the world. The disease is characterized by a diverse clinical course, including early skin lesions such as erythema migrans, and late joint, neurological, cardiac, and, less frequently, chronic complications. The pathogenesis of Lyme disease is associated with the invasion of tissues by the spirochetes and their ability to evade the host immune response, leading to chronic inflammation. Diagnosis relies on a combination of clinical assessment and serological testing, while considering the limitations of false positive and negative results. Standard treatment includes antibiotic therapy tailored to the stage of disease. Prevention plays a key role and includes the use of repellents, appropriate clothing, environmental monitoring, and public education and awareness in endemic areas. Effective prevention and early diagnosis are essential to reduce morbidity and clinical complications.